Supercritical CO2 extract from Microalga Tetradesmus obliquus: the effect of high-pressure pre-treatment - Vladić, Jelena (2022)
High-pressure pre-treatment followed by supercritical carbon dioxide (ScCO2 ) extraction (300 bar, 40 ◦C) was applied for the attainment of the lipophilic fraction of microalga Tetradesmus obliquus. The chemical profile of supercritical extracts of T. obliquus was analyzed by ultra-highperformance liquid chromatography–high-resolution mass spectrometry with electrospray ionization (UHPLC-ESI-HRMS). Moreover, the impact of ScCO2 on the microbiological and metal profile of the biomass was monitored. The application of the pre-treatment increased the extraction yield approximately three-fold compared to the control. In the obtained extracts (control and pre-treated extracts), the identified components belonged to triacylglyceroles, fatty acid derivatives, diacylglycerophosphocholines and diacylglycerophosphoserines, pigments, terpenes, and steroids. Triacylglycerols (65%) were the most dominant group of compounds in the control extract. The pre-treatment decreased the percentage of triacylglycerols to 2%, while the abundance of fatty acid derivatives was significantly increased (82%). In addition, the pre-treatment led to an increase in the percentages of carotenoids, terpenoids, and steroids. Furthermore, it was determined that ScCO2 extraction reduced the number of microorganisms in the biomass. Considering its microbiological and metal profiles, the biomass after ScCO2 can potentially be used as a safe and important source of organic compounds.